(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The work shows that after a partial hepatectomy the relative volume of T zone increases in the spleen of rats and domestic hens, which leads to the increase of lymphocytes proliferation intensity in the given region. The quantity of plasmatic cells, on the contrary, decreases.